2020
DOI: 10.1016/j.ejmp.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Short-duration dynamic FDG PET imaging: Optimization and clinical application

Abstract: We aimed to investigate whether short dynamic PET imaging started at injection, complemented with routine clinical acquisition at 60-min post-injection (static), can achieve reliable kinetic analysis. Methods: Dynamic and static 18F-2-fluoro-2-deoxy-D-glucose (FDG) PET data were generated using realistic simulations to assess uncertainties due to statistical noise as well as bias. Following image reconstructions, kinetic parameters obtained from a 2-tissue-compartmental model (2TCM) were estimated, making use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“…Samimi et al reported ~10% bias for kinetic parameters estimation when decreasing the dynamic scanning time to 5 minutes supplemented by a whole body PET scan 60 minutes postinjection. 30 A similar trend was also reported in two other studies where the bias in K i estimates was ~5% 28 and 9% 27 when decreasing dynamic scanning time from 60 to 40 minutes and from 60 to 30 minutes respectively.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Samimi et al reported ~10% bias for kinetic parameters estimation when decreasing the dynamic scanning time to 5 minutes supplemented by a whole body PET scan 60 minutes postinjection. 30 A similar trend was also reported in two other studies where the bias in K i estimates was ~5% 28 and 9% 27 when decreasing dynamic scanning time from 60 to 40 minutes and from 60 to 30 minutes respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The quantitative evaluation of predicted images showed less than 7% bias for , and less than 14% bias for in most brain regions. Samimi et al reported ~10% bias for kinetic parameters estimation when decreasing the dynamic scanning time to 5 min supplemented by a whole body PET scan 60 min post-injection 30 . A…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the dPET acquisition time might be reduced by a factor of 2, in the routine clinical diagnosis SUV derived from static PET imaging is still of importance. Samimi et al [32] suggested a short dPET coupled with static PET acquisition as an alternative approach. However, its feasibility in total-body dPET imaging was unknown.…”
Section: Discussionmentioning
confidence: 99%